An alleged murder due to blunt head injury from a viewpoint of forensic investigation: a case report - Taufik Suryadi; Kulsum (Surgical Residency Program Syiah Kuala University, 2021)
Background: Blunt violence on the head often occurs in the community, which often causes fatal conditions and even death. Death due to blunt force on the head can be caused by intracranial bleeding or destruction of brain tissue. Case description: A case of suspected murder was reported due to blunt violence on the victim's head with the initials RA, 16 years old, a student at an official school. On forensic medical examination found signs of blunt violence in the form of bruises on the forehead and face, and the results of an autopsy found the destruction of the bones forming the face, fracture of the skull with the release of brain tissue. In the police investigation, the suspect admitted to committing violence with a kick on the head of the victim using shoes without other tools. There was a mismatch between the strength of the violence recognized by the suspect and the autopsy findings so that the forensic examination focused on seeing whether blunt violence that occurred on the victim could result in death or not. Conclusion: It is necessary to deepen police checks on suspects about how violence was carried out, how the power of violence was carried out, and what were the motives for violence. During the trial, the panel of judges stated that there was a possibility that the perpetrators would use hard objects to attack the victim.